1994
DOI: 10.2134/jeq1994.00472425002300050013x
|View full text |Cite
|
Sign up to set email alerts
|

Diagenesis of Organic Matter in a Wetland Receiving Hypereutrophic Lake Water: I. Distribution of Dissolved Nutrients in the Soil and Water Column

Abstract: A recently constructed marsh from previously drained agricultural land currently receives nutrient-laden water from adjacent hypereutrophic Lake Apopka, located in central Florida. Lake water is allowed to cycle through the marsh, allowing settlement of participate organic matter, which forms a floe sediment layer on the native peat soil surface. The water leaving the marsh is returned to the lake after a retention time of 3 to 12 d. This study determined changes in temporal and spatial distribution of selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…The capacity of the soil to retain nutrients varies depending on the physical and chemical soil characteristics, such as the cation exchange capacity (Lance 1972), the soil sorption properties (D´Angelo and Reddy 1994), and the form of nutrient in the throughflowing water (Lance 1972). Ammonium (NH 4 + ) can be retained into cation exchange sites of the soil (Lance 1972, Heikkinen et al 1994, while nitrate (NO 3 -) generally remains in soluble form, unless assimilated by vegetation or microbial communities.…”
Section: The Key-factors Controlling the Retention Capacity Of Peatlamentioning
confidence: 99%
See 2 more Smart Citations
“…The capacity of the soil to retain nutrients varies depending on the physical and chemical soil characteristics, such as the cation exchange capacity (Lance 1972), the soil sorption properties (D´Angelo and Reddy 1994), and the form of nutrient in the throughflowing water (Lance 1972). Ammonium (NH 4 + ) can be retained into cation exchange sites of the soil (Lance 1972, Heikkinen et al 1994, while nitrate (NO 3 -) generally remains in soluble form, unless assimilated by vegetation or microbial communities.…”
Section: The Key-factors Controlling the Retention Capacity Of Peatlamentioning
confidence: 99%
“…Peat soils usually have high cation exchange capacity (CEC), which enables a considerable potential to the retention of NH 4 + (Heikkinen et al 1994). The effective cation exchange capacity is generally highest in the peat surface layer (Ronkanen and Kløve 2009), however, water table level fluctuations may affect the CEC (Lance 1972, D´Angelo andReddy 1994). Flooding of aerobic peat soil may result in NH 4 + release, because anaerobic bacteria has lower requirements for N, leaving more NH 4 + available for transport from the soil to the water column (D´Angelo and Reddy 1994).…”
Section: The Key-factors Controlling the Retention Capacity Of Peatlamentioning
confidence: 99%
See 1 more Smart Citation
“…They were air-dried at room temperature (25)(26)(27)(28) • C) and then passed through 10-mesh polyethylene sieve to remove stones and other debris. A portion (about 50 g) was ground in an agate grinder and sieved through 100-mesh polyethylene sieve before chemical analysis.…”
Section: Sediments Sampling and Elements Analysismentioning
confidence: 99%
“…Water temperature is known to indirectly influence P release in sediments [26], with a high temperature boosting the activity of some substances and accelerating physical, chemical, and biological reactions such as the diffusion and degradation of organic matter. Microorganisms can also decompose organic P in sediments into inorganic P and convert insoluble phosphorus compounds into soluble ones and higher metabolic rates can accelerate the degradation of organic matter [27], thus promoting P release from sediments. For N release, Liu et al [28] reported that water temperature can influence degradation speed, when temperatures drop too low, the degradation of N in deeper-sediments can cease altogether.…”
Section: Water Temperaturementioning
confidence: 99%